IMPROVING READING ABILITY THROUGH GROUP WORK ACTIVITIES OF THE THIRD YEARS STUDENTS AT SMP NEGERI 13 KOTA BENGKULU IN ACADEMIC YEAR 1996 / 1997 - Zarawin Zarawin (Linguists : Journal Of Linguistics and Language Teaching, 2015)
This study deals with the use of group work activities in order to improve reading readingability of the third years student at SMP Negeri 13 Kota Bengkulu academic year 1996 /1997. The main purpose of the study was to find out 1) the student achievement in readingability through group work activities. 2) whether or not group work activities technique iseffective in improving reading ability.The population of this study was four classes of the third year students. From the four classesthe writer took two classes of 25 students were taken randomly so the sample consist of 50student. In doing his research the writer did the experiment, the writer divided the samplestudents into the groups. Group A ( experimental Group ) and group B ( control group )both of these group were given pre – test and post test . the post test was given after theteaching experiment. In analyzing data the writer used t – test to compare before and aftertreatment.The result of this study showed that there was a progress made by goup A ( experimentalgroup ) with the gain t = 5.34 while group B ( control group ) got 1.67 the value of t –table of df=24 was 1.74. since the value of the gained t was higher than the value of t –table this means that thr group work activities can be proved effectively.Beside that, the writer also found that there was a significant difference between group A( experimental group ) and group B ( control group ). The value of gained t was 4.02 whilethe value of t – table of df = 24 is 2.06. it means that 4.02 > 2.06 so the second hypothesisis retained.